Rapid and high seroprotection rates achieved with a tri-antigenic Hepatitis B vaccine in healthy young adults: Results from a Phase IV study. Issue 8 (22nd February 2021) - Atsmon, Jacob; Machluf, Nathalie; Yayon-gur, Vered; Sabbah, Cyril; Spaans, Johanna N.; Yassin-Rajkumar, Bebi; Anderson, David E.; Popovic, Vlad; Diaz-Mitoma, Francisco
Highlights: Peak immune response was achieved one month after the third vaccination. TAV may enhance immunogenicity in adults with typically poor or delayed response to second-generation vaccines. Abstract: Background: Sci-B-Vac® is a tri-antigenic recombinant Hepatitis B vaccine (TAV) containing the small (s), medium (pre-S2) and large (pre-S1) hepatitis B surface (HBs) antigens. To comply with vaccine licensure, a new reference standard batch was qualified by characterizing the seroprotection rate (SPR) for anti-HBs titers ≥10 mIU/mL, following vaccination. Methods: Ninety-one healthy adults aged 20–40 years were enrolled in an open label, single-arm phase IV study receiving three IM doses of 10 μg TAV at 0, 1 and 6 months. Immunogenicity was evaluated monthly and at 7, 9 and 12 months. The primary endpoint to qualify the reference standard was an SPR ≥95% by month 7. Secondary endpoints were proportion of high responders (anti-HBs titers ≥100 mIU/mL) and geometric mean concentrations (GMC) of HBs antibodies each month. Participants were followed for safety to month 12. Results: The primary endpoint was met 2 months after the second dose at month 3 [SPR 98.8%; 95% CI: 93.7%, 99.7%]. Proportion of high responders at months 3 and 7 were 81.4% and 97.6%, respectively. GMC at months 3 and 7 were 413.6 mIU/mL and 6799.9 mIU/mL, respectively. TAV was safe and well-tolerated. Conclusions: The new reference standard batch of TAV was qualified successfully, demonstrating efficacy, a favorable safety profile and a rapid onset of seroprotection, including after two vaccine doses. Clinical trial registry: NCT04179786.